Contrast-Enhancement of the Anterior Eye Segment in Patients with Retinoblastoma: Correlation between Clinical, MR Imaging, and Histopathologic Findings - de Graaf, P.; van der Valk, P.; Moll, A.C.; Imhof, S.M.; Schouten-van Meeteren, A.Y.N.; Knol, D.L.; Castelijns, J.A. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: AES contrast-enhancement is recognized in a substantial number of retinoblastoma-affected eyes. We retrospectively investigated the histopathologic basis of AES contrast-enhancement on MR images in retinoblastoma. MATERIALS AND METHODS: Pretreatment contrast-enhanced MR images were obtained from 42 children with retinoblastoma. Forty-two enucleated eyes were included in this study, AES enhancement was evaluated by using a 3-point score, and these data were correlated with clinical, MR imaging, and histopathologic findings. Additionally, 14 specimens were immunohistochemically analyzed for CD31, VEGF, and Flt-1 expression. Statistical correlations with AES enhancement were assessed by using a linear-by-linear association test and univariate and multivariate ordinal regressions. RESULTS: The degree of abnormal AES enhancement was moderate in 15 (36%) eyes and strong in 14 (33%) eyes, whereas 13 (31%) eyes showed normal AES enhancement. In multivariate analysis, the degree of AES enhancement showed statistically significant correlations with iris surface-vessel count (P = .05) and optic nerve invasion (P = .04) in the enucleated eye and with tumor volume (P = .02) as detected on MR imaging. No significant associations between AES enhancement and VEGF expression in the iris were observed. Flt-1 (P = .04) staining in iris stroma and IA as detected with CD31 staining (P = .009) both yielded a statistically significant positive correlation with abnormal AES enhancement. CONCLUSIONS: The degree of abnormal AES enhancement on MR imaging in retinoblastoma reflects angiogenesis in the iris. AES enhancement is also a hallmark of advanced retinoblastoma because its degree correlates with tumor volume and optic nerve invasion. ACanterior chamberAESanterior eye segmentBOBblood-ocular barrierCcorneaMVDmicrovessel densityFlt-1VEGF-receptor-1H&Ehematoxylin-eosinHIF-1hypoxia-inducible factorHPFhigh-power fieldIAiris angiogenesisIOPintraocular pressureVEGFvascular endothelial growth factor